Engrailed 1 deficiency induces changes in ciliogenesis during human neuronal differentiation - Sina Hembach; Sebastian Schmidt; Tanja Orschmann; Ingo Burtscher; Heiko Lickert; Florian Giesert; Daniela Vogt Weisenhorn; Wolfgang Wurst (Neurobiology of Disease, 2024)
A key pathological feature of Parkinson’s Disease (PD) is the progressive degeneration of dopaminergic neurons (DAns) in the substantia nigra pars compacta. Considering the major role of EN1 in the development and maintenance of these DAns and the implications from En1 mouse models, it is highly interesting to study the molecular and protective effect of EN1 also in a human cellular model. Therefore, we generated EN1 knock-out (ko) human induced pluripotent stem cell (hiPSCs) lines and analyzed these during neuronal differentiation. Although the EN1 ko didn’t interfere with neuronal differentiation and generation of tyrosine hydroxylase positive (TH+) neurons per se, the neurons exhibited shorter neurites. Furthermore, mitochondrial respiration, as well as mitochondrial complex I abundance was significantly reduced in fully differentiated neurons. To understand the implications of an EN1 ko during differentiation, we performed a transcriptome analysis of human neuronal precursor cells (hNPCs) which unveiled alterations in cilia-associated pathways. Further analysis of ciliary morphology revealed an elongation of primary cilia in EN1-deficient hNPCs. Besides, also Wnt signaling pathways were severely affected. Upon stimulating hNPCs with Wnt which drastically increased EN1 expression in WT lines, the phenotypes concerning mitochondrial function and cilia were exacerbated in EN1 ko hNPCs. They failed to enhance the expression of the complex I subunits NDUFS1 and 3, and now displayed a reduced mitochondrial respiration. Furthermore, Wnt stimulation decreased ciliogenesis in EN1 ko hNPCs but increased ciliary length even further. This further highlights the relevance of primary cilia next to mitochondria for the functionality and correct maintenance of human DAns and provides new possibilities to establish neuroprotective therapies for PD.